Archeologia dell'inferno. L'Aldilà nel mondo antico vicino- orientale e classico (1987)
Contributi di G. Scandone Matthiae, J. Bottéro, G. F. Del Monte, P. Xella, S. Ribichini, Th. Podella, C. Grottanelli, H.-J. Klimkeit, F.Saracino, B.Zannini Quirini;